Urban Planning for the Integration of Refugees: The Importance of Local Factors - Seethaler-Wari, Shahd (2018)
Housing location is one of several characteristics that play a significant role in the future integration of asylum-seekers. Many of these characteristics or institutional arrangements are spatialized aspects relevant to urban planning. Drawing on experiences from fieldwork in Göttingen, a mid-sized city in the German Federal state of Lower-Saxony 2016–2018, this article demonstrates the local challenges, strategies and their resulting institutional arrangements on various aspects of asylum-seekers’ lives. It discusses the influence of those arrangements on the development of their social circles, and on their access to different resources, influencing their participation in and interaction with the social and urban life of their host cities; thereby influencing their integration processes. To do so, the article addresses local factors that are significant for urban planners to include into an integration plan. It observes the role urban planning can play in preventing aspects of segregation in the various life domains of refugees and in providing urban contexts that facilitate integration in European cities. The first assumption of this article is that integration, refugees’ attitudes towards it, and an urban context that can facilitate it start from day one of the arrival of new comers in their host city/town. The second assumption is that integration happens on the local level of the city, and more specifically on the level of the host neighborhood.